From Learning on Mannequins to Practicing on Patients: Nursing Students' First-Time Experience of Clinical Placement in Jordan - Deema Mahasneh RGN, MSc, PhD; Noordeen Shoqirat RGN, Neuro-SN, MSc, PhD; Arwa Alsaraireh DNP, RN; Charleen Singh PhD, FNP-BC, CWOCN, RN; Lee Thorpe MSN, RN, CPHQ (SAGE Publishing, 2021)
Introduction Although clinical nursing placement is an indispensable component of student nurses' education, data on students' first clinical experiences is scarce in developing countries. Objectives The study aim is to uncover nursing students' first-time clinical placement experience and identify related influencing factors in Jordan. Method s: Focus group discussions (n=4) were used. Results The results showed that the transition from learning with mannequins to practicing on real patients in the clinical placement involved both effective learnings through hands-on practice to dealing with clinical challenges. Students perception of nursing ranged from positive comments such as "humanistic" and "nursing almost medicine" to negative images such as "nursing is all about bedside care" and "nursing has poor social status." Conclusion Students' experience in their first clinical placement is multifaceted, and incorporation of student's perspective in the first clinical placement is a crucial component of educational planning.